The impact of a 100% smoke-free law on the health of hospitality workers from the city of Neuquén, Argentina. Issue 2 (8th April 2010) - Schoj, Veronica; Alderete, Mariela; Ruiz, Ernesto; Hasdeu, Santiago; Linetzky, Bruno; Ferrante, Daniel
Abstract : Objectives: The objective of this study was to evaluate the impact of 100% smoke-free environment legislation on respiratory and sensory irritation symptoms and respiratory function among bar and restaurant workers from the city of Neuquén, Argentina. Methods: Pre-ban and post-ban studies without a comparison group in an Argentinean city were conducted. A baseline survey and spirometric measurements were performed with a total of 80 bar and restaurant workers 1 month before (October 2007) and 3 months after (March 2008) the implementation of the new 100% smoke-free legislation. Results: A significant reduction in secondhand smoke exposure was observed after the enactment and enforcement of the new legislation, and an important reduction in respiratory symptoms (from a pre-ban level of 57.5% to a post-ban level of only 28.8%). The reduction of sensory irritation symptoms was even higher. From 86.3% of workers who reported at least one sensory irritation symptom in October 2007, only 37.5% reported the same symptoms in March 2008. Also, data obtained by spirometry showed a significant forced vital capacity increase. Conclusions: Consistent with other studies, 100% smoke-free legislation improved short-term health outcomes in the sample and should be implemented nationwide. Furthermore, undertaking this study has been highly important in promoting 100% smoke-free environment legislation at the workplace as a legitimate right of hospitality workers, and in reducing social acceptance of designated smoking areas in bars and restaurants.